An Exploration of EFL Teachers' Awareness of the Sources of Pedagogical Knowledge in a Teacher Education Program - Macías Diego Fernando (Universidad Nacional de Colombia, 2013)
<span style="font-size: 10.0pt; font-family: ";Verdana";,";sans-serif";; mso-fareast-font-family: ";Times New Roman";; mso-bidi-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: ES-CO; mso-bidi-language: AR-SA;" lang="EN-US">This project set out to investigate the extent to which the sources of English as a foreign language teachers' pedagogical knowledge are acknowledged and addressed in a teacher education program in a public university in Colombia. It involved the participation of teacher educators and novice teachers as well as the analysis of documents. This research followed a qualitative design with an interpretive approach to inquiry, and the data used were semi-structured interviews and official documents. The results indicate that while most of the teacher educators appeared to be aware of the many sources of teachers' pedagogical knowledge, novice teachers emphasized their initial teacher education and teaching experience as the only sources of their pedagogical knowledge. <span style="font-size: 10.0pt; font-family: ";Verdana";,";sans-serif";; mso-fareast-font-family: ";Times New Roman";; mso-bidi-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: ES-CO; mso-bidi-language: AR-SA;" lang="EN-US">Este proyecto buscó investigar hasta qué punto las diferentes fuentes de conocimiento pedagógico de los docentes de inglés como lengua extranjera son reconocidas y abordadas en un programa de formación inicial en una universidad pública en Colombia. El proyecto involucró la participación de formadores de docentes y docentes principiantes y el análisis de documentos. La investigación siguió un diseño cualitativo con un enfoque interpretativo y los datos utilizados fueron entrevistas semiestructuradas y documentos oficiales. Los resultados indican que mientras la mayoría de los formadores de docentes parecían ser conscientes de las muchas fuentes del conocimiento pedagógico de los docentes, los docentes principiantes enfatizaron su educación inicial como docentes y la experiencia docente como las únicas fuentes de su conocimiento pedagógico.